Pengaruh Perubahan Strategi Pemasaran, Kepemimpinan Transfomasional dan Organsiasi Pembelajar terhadap Kinerja Perbankan Syariah di DKI Jakarta - Muhammad Richo Rianto (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to know influence marketing strategic change, transformational leadership and organization learning on performance of Indonesian Islamic. This study uses quantitative research with a purposive sampling technique with a population of 14 Indonesian islamic banks. The targeted unit of analysis is the Islamic banks manager. There were 100 questionnaires returned and 3 of them did not meet the requirements, so only 97 were used in this study. This study uses SmartPLS 3 to test the hypothesis. Findings - This research shows that strategic change, transformational leadership and organization learning affect on firm performance. Islamic banks managers must be able to identify the importance of change for the company, because of the big risks. Supporting leadership skills and organization learning in companies makes Islamic banking better competitive. Similar research is usually carried out in manufacturing and service companies and is carried out in developed countries (Europe, America and Africa). The focus of this research is the development of strategic change supported by transformational leadership and organization learning on performance. This research was also conducted for the first time in Asia with the object of Islamic banks in Jakarta - Indonesia.